Pharmacological Inhibition of Astrocytic Transglutaminase 2 Facilitates the Expression of a Neurosupportive Astrocyte Reactive Phenotype in Association with Increased Histone Acetylation - Thomas Delgado; Jacen Emerson; Matthew Hong; Jeffrey W. Keillor; Gail V. W. Johnson (Biomolecules)
Astrocytes play critical roles in supporting structural and metabolic homeostasis in the central nervous system (CNS). CNS injury leads to the development of a range of reactive phenotypes in astrocytes whose molecular determinants are poorly understood. Finding ways to modulate astrocytic injury responses and leverage a pro-recovery phenotype holds promise in treating CNS injury. Recently, it has been demonstrated that ablation of astrocytic transglutaminase 2 (TG2) shifts reactive astrocytes towards a phenotype that improves neuronal injury outcomes both in vitro and in vivo. Additionally, in an in vivo mouse model, pharmacological inhibition of TG2 with the irreversible inhibitor VA4 phenocopied the neurosupportive effects of TG2 deletion in astrocytes. In this study, we extended our comparisons of VA4 treatment and TG2 deletion to provide insights into the mechanisms by which TG2 attenuates neurosupportive astrocytic function after injury. Using a neuron–astrocyte co-culture model, we found that VA4 treatment improves the ability of astrocytes to support neurite outgrowth on an injury-relevant matrix, as we previously showed for astrocytic TG2 deletion. We hypothesize that TG2 mediates its influence on astrocytic phenotype through transcriptional regulation, and our previous RNA sequencing suggests that TG2 is primarily transcriptionally repressive in astrocytes, although it can facilitate both up- and downregulation of gene expression. Therefore, we asked whether VA4 inhibition could alter TG2’s interaction with Zbtb7a, a transcription factor that we previously identified as a functionally relevant TG2 nuclear interactor. We found that VA4 significantly decreased the interaction of TG2 and Zbtb7a. Additionally, we assessed the effect of TG2 deletion and VA4 treatment on transcriptionally permissive histone acetylation and found significantly greater acetylation in both experimental groups. Consistent with these findings, our present proteomic analysis further supports the predominant transcriptionally repressive role of TG2 in astrocytes. Our proteomic data additionally unveiled pronounced changes in lipid and antioxidant metabolism in astrocytes with TG2 deletion or inhibition, which likely contribute to the enhanced neurosupportive function of these astrocytes.